Strategi Transformasi Ekonomi Nelayan dan UMKM melalui Kolaborasi dan Networking Berbasis Blue Economy di Lamongan - Aditya Suryan Nanda; Pramandyah Fitah Kusuma (Universitas Negeri Surabaya, 2026)
This research aims to analyze the role of collaboration and networking in encouraging the economic transformation of MSMEs and fishermen based on the Blue Economy in Lamongan. Although the coastal area of Lamongan has abundant marine resource potential, the welfare of coastal communities still faces several challenges, including limited market access, weak distribution networks, lack of capital support, and low mastery of seafood processing technology. This research uses a qualitative approach with an exploratory case study design conducted in Lamongan. Data were obtained through in-depth interviews with fishermen, MSME actors, local government, academics, and the private sector, complemented by participatory observation and documentation studies. The results show that multi-actor collaboration among the government, the private sector, academics, and local communities, along with strong networking within fishermen and MSME groups, plays an important role in strengthening the economic competitiveness of coastal communities. Support in the form of product certification, training, equipment assistance, and expanded market access improves production quality, strengthens marketing, and expands business networks to international markets, such as the export of rajungan meat to the United States and shrimp paste products to Europe. Collaboration and networking also strengthen the long-term socio-economic resilience of fishermen and MSMEs through the implementation of zero-waste principles, product diversification, and sustainable marine resource management. This research contributes theoretically to the Blue Economy literature by emphasizing the integration of collaboration and networking in coastal economic transformation and provides practical recommendations for strengthening an inclusive and sustainable blue economy ecosystem in Lamongan.